2009
DOI: 10.1364/oe.17.013335
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional transmission in non-symmetric gratings containing metallic layers

Abstract: Abstract:The mechanism of achieving unidirectional transmission in the gratings, which only contain isotropic dielectric and metallic layers, is suggested and numerically validated. It is shown that significant transmission in one direction and nearly zero transmission in the opposite direction can be obtained in the same intrinsically isotropic gratings as those studied recently in A. E. Serebryannikov and E. Ozbay, Opt. Express 17, 278 (2009), but at a non-zero angle of incidence. The tilting, non-symmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 21 publications
4
67
0
Order By: Relevance
“…In the gratings made of Drude metals or composites, the actual thresholds have different locations as compared to the classical case that is associated with dielectric gratings (Serebryannikov & Ozbay, 2009). In the PCGs with either dielectric or metallic rods, the actual thresholds can also be affected by location of the stop bands of the PC (Serebryannikov, 2006;Serebryannikov, 2009).…”
Section: Asymmetry In Threshold Locationmentioning
confidence: 99%
“…In the gratings made of Drude metals or composites, the actual thresholds have different locations as compared to the classical case that is associated with dielectric gratings (Serebryannikov & Ozbay, 2009). In the PCGs with either dielectric or metallic rods, the actual thresholds can also be affected by location of the stop bands of the PC (Serebryannikov, 2006;Serebryannikov, 2009).…”
Section: Asymmetry In Threshold Locationmentioning
confidence: 99%
“…In several papers published recently [20][21][22][23][24] authors claimed nonreciprocity on the basis of various effects observed in the behavior electromagnetic propagation in linear, time-independent structures consisting of materials described by symmetric (i.e. reciprocal) permittivities and/or permeabilities.…”
Section: Introductionmentioning
confidence: 99%
“…[25] that in the interpretation of the behavior observed in silicon photonic circuit based on asymmetric mode conversion observed experimentally [24] the term "nonreciprocal" has been used incorrectly. Based on the validity of the Lorentz nonreciporocity theorem statement we believe that the interpretation of the effects observed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there were attempts to achieve asymmetric but still reciprocal transmission by using conventionally isotropic, linear, and lossy or lossless materials. For instance, the asymmetric transmission of linearly polarized waves can be realized by using diffractive nonsymmetrical volumetric gratings based on photonic crystals or metals, [ 6 ] using nonsymmetrical two layered metallic structures, [ 7 ] using nonsymmetrical metallic gratings supporting surface plasmons, [ 8 ] and using dielectric gratings. [ 9 ] The asymmetric transmission of circularly polarized waves has been demonstrated at normal incidence by using a multilayered structure [ 7,10 ] and by using a planar chiral structure (PCS) consisting of single layer of metaatoms.…”
mentioning
confidence: 99%